2007
DOI: 10.1107/s1600536807028978
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxyanilinium hydrogensulfate

Abstract: Key indicators: single-crystal X-ray study; T = 293 K; mean (C-C) = 0.003 Å; R factor = 0.030; wR factor = 0.099; data-to-parameter ratio = 18.5.In the title compound, C 6 H 8 NO + ÁHSO 4 À , there is an intricate cation-cation, cation-anion and anion-anion three-dimensional hydrogen-bond network. Refinement R[F 2 > 2(F 2 )] = 0.030 wR(F 2 ) = 0.099 S = 1.14 2241 reflections 121 parameters 1 restraint H-atom parameters constrained Á max = 0.32 e Å À3 Á min = À0.45 e Å À3 Absolute structure: Flack (1983), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The methylanilinium is already reported with nitrate (Benali-Cherif et al, 2007), picrate (Muthamizhchelvan et al, 2005) and dihydrogenphosphate (Fábry et al, 2002).…”
Section: Related Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…The methylanilinium is already reported with nitrate (Benali-Cherif et al, 2007), picrate (Muthamizhchelvan et al, 2005) and dihydrogenphosphate (Fábry et al, 2002).…”
Section: Related Literaturementioning
confidence: 77%
“…For related literature, see: Benali-Cherif et al (2007); Bouacida et al (2005aBouacida et al ( ,b,c, 2006Bouacida et al ( , 2007Fá bry et al (2002); Hill (1998); Kagan et al (1999); Koutselas et al (1996); Mayer et al (1999); Mazeaud et al (2000); Mitzi et al (1998); Muthamizhchelvan et al (2005); Raptopoulou et al (2002). Table 1 Hydrogen-bond geometry (Å , ).…”
Section: Related Literaturementioning
confidence: 99%
“…For background to inorganic-organic hybrid materials, see: Benali-Cherif, Allouche et al (2007); Benali-Cherif, Kateb et al (2007); Messai et al (2009); Cherouana et al (2003). Changes in illuminated volume were kept to a minimum, and were taken into account (Gö rbitz, 1999) by multi-scan interframe scaling.…”
Section: Related Literaturementioning
confidence: 99%
“…For related structures, see: Benali-Cherif et al (2007, 2009. For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…The crystal structure of the title compound was determined as part of a project focusing on the role of anions when combined with alkylammonium or arylammonium cations. The structures of the related compounds p-toluidinium nitrate (Benali-Cherif et al, 2009) and o-toluidinium nitrate (Benali-Cherif et al, 2007) have been reported in the literature.…”
Section: S1 Commentmentioning
confidence: 99%